What does it take and mean to be a finance professional in Finland? : Social representations of investing and the identity and perceptions of Finnish private banking professionals - Laine, Karolina (My University, 2018)
Motivated by the existence of multiple conflicting representations of investing and investors in society and the lack of research on the social and cultural aspects of investing, this study set out to investigate how Finnish private banking professionals perceive themselves, their work and investing in general with the aim to contribute to the understanding of how factors other than “rational” wealth-maximization might influence people’s investment decisions. Drawing on social psychological theories on social identity, social representations and discourses as drivers of human behavior, the study proposes an alternative theoretical framework for explaining investing behavior. Further, reviewing earlier research on representations of investing, investors and financial markets, the study provides a comprehensive mapping of the sociocultural milieu for investing in western societies. The empirical data of the study consists of semi-structured, conversational interviews with the above-mentioned professionals and was analyzed using both content analysis and methods of discourse analysis. The results reveal that the positively associated, socially prestigious roles of a finance expert and an advisor form the basis for Finnish private banking professionals’ identities, but the socially problematic role of a salesman must be integrated into the identity as well, resulting in tensions which must be managed successfully to qualify as a “real” professional. Further, the professionals tend to see investing in the manner of neoclassical finance theories, i.e. in terms of profit and risk, and as individualistic and thus socially unproblematic, intrinsically valuable, rational and responsible management and maximization of wealth. The results also suggest the existence of multiple alternative, conflicting social representations of investing in society. Overall, the results fit the developed theoretical framework: the professionals’ perceptions correlate with the positive and neutral representations of investing described in earlier research, while the alternative, conflicting social representations of investing rejected as misconceptions correlate with the negative representations described in the earlier research. This implies the social and cultural aspects of investing are indeed meaningful and should not be ignored. For example, social representations might explain the “irrational” investing typically considered an anomaly. Further, in practice influencing perceptions might prove more effective than economic motivators in changing investing behavior. All in all, this study serves as a useful starting point for practical applications as well as for further scientific inquiry into the social and cultural aspects of investing and financial phenomena.
Keywords: investing, social identity, social representation